2012
DOI: 10.3390/ma5101954
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Photorefraction of Doped Lithium Niobate Crystals

Abstract: The recent advances in the photorefraction of doped lithium niobate crystals are reviewed. Materials have always been the main obstacle for commercial applications of photorefractive holographic storage. Though iron-doped LiNbO3 is the mainstay of holographic data storage efforts, several shortcomings, especially the low response speed, impede it from becoming a commercial recording medium. This paper reviews the photorefractive characteristics of different dopants, especially tetravalent ions, doped and co-do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 93 publications
2
44
0
1
Order By: Relevance
“…Although we argue that electrostatic interactions play only a minor role in our experiments, we expect such mechanisms to become particularly important in doped ferroelectric crystals (i.e., Fe:LiNbO 3 ), where a significant contribution from photoinduced charges is expected. 29 In conclusion, we have demonstrated that the strain of graphene on lithium niobate can be controlled at the microscopic scale by laser irradiation. We argue that the observed effect is mainly due to the large thermal coefficient mismatch between the graphene and the substrate leading to relaxation of intrinsic strain.…”
Section: Dmentioning
confidence: 97%
“…Although we argue that electrostatic interactions play only a minor role in our experiments, we expect such mechanisms to become particularly important in doped ferroelectric crystals (i.e., Fe:LiNbO 3 ), where a significant contribution from photoinduced charges is expected. 29 In conclusion, we have demonstrated that the strain of graphene on lithium niobate can be controlled at the microscopic scale by laser irradiation. We argue that the observed effect is mainly due to the large thermal coefficient mismatch between the graphene and the substrate leading to relaxation of intrinsic strain.…”
Section: Dmentioning
confidence: 97%
“…However, these light induced optical effects in CLN can be minimized to a significant extent by operating the device at higher temperature (~180 °C) or by using defect controlled stoichiometric LN having lesser intrinsic defects and impurities [23]. When grown in the near-stoichiometric form (nSLN, Li/Nb ~ 1) the optical properties improve significantly (Table 1) as a result of the decrease in the defect concentration [30,[46][47][48][49][50][51][52]. So nSLN is a better choice for nonlinear frequency conversion, as well as photo-refractive and holographic data storage applications [53,54] in comparison to CLN.…”
Section: Effect Of Intrinsic Defect On Propertiesmentioning
confidence: 99%
“…[93][94][95][96][97][98] The properties of LN doped with optical damage resistant ions were first summarized in a review paper 10 and later in a book by Volk et al 99 Recently, Kong et al 100 reviewed advances in the photorefraction of doped LN, focusing on tetra-, penta-, and hexavalent ions, including doubly-and even triply-doped crystals. They concluded that LN triply doped by Zr, Fe, and Mn shows excellent non-volatile holographic storage properties, and V and Mo single-doped LN have fast response and multi-wavelength storage characteristics.…”
Section: Other Divalent Trivalent and Tetravalent Odr Dopantsmentioning
confidence: 99%